Genetic correlations of days open with milk yield and metabolic weight in Holstein and Brown swiss cows - Ríos Utrera, Ángel; Calderón Robles, René Carlos; Galavíz Rodríguez, José Reyes; Vega Murillo, Vicente Eliezer; Lagunes Lagunes, Juvencio (Venezuela, 2015)
The aim of the present study was to estimate (co)variance components and genetic correlations of days open with milk yield per lactation, lactation length and metabolic weight in Holstein and Brown Swiss cows under subtropical conditions of Mexico. Cows were kept in an intensive rotational grazing system in which the principal feed was Star grass (Cynodon plectostachyus). Cows were milked twice daily, by machine. Analyses of data were made applying a series of bivariate animal models in the MTDFREML program. Models for days open, milk yield per lactation and metabolic weight included breed of cow, calving year, calving season and lactation number as fixed environmental effects, and animal direct genetic, cow’s permanent environmental, and residual as random effects. For lactation length the model included the same fixed and random effects, except cow’s permanent environmental effect. The estimates of genetic correlations of days open with milk yield per lactation and metabolic weight were moderate and positive (0.45 and 0.33, respectively), suggesting that genes that control milk yield per lactation and metabolic weight also control days open. Estimates of phenotypic and permanent environmental correlations were smaller than estimates of genetic correlations. Results of the present study evidence that poor genetic potential for reproductive performance is associated with high genetic potential for milk production and metabolic weight.
Correlaciones genéticas de días abiertos con producción de leche y peso metabólico en vacas Holstein y Pardo Suizo
Keywords: Genetic correlations; Days open; Milk yield; Cattle; Subtropics; Metabolic weight; Universidad del Zulia (LUZ); Universidad de Los Andes (ULA); Correlaciones genéticas; Días abiertos; Producción de leche; Bovinos; Subtrópico; Peso metabólico; Revista Científica; Revista Científica: Producción Animal / Animal Production; Medio Ambiente; Revistas